Community‐based screening to detect school readiness problems in very preterm children. (20th September 2017) - Rajput, Nitin; McKinlay, Chris; Purdie, Gordon; Filipovska, Julia; Battin, Malcolm; Patel, Harshad; Tuohy, Pat
Abstract : Aim: Very preterm (VPT) children (≤32 weeks) have school readiness difficulties across multiple domains, but routine follow‐up is often limited. We assessed the performance of VPT children on the Before School Check (B4SC), a community‐based screening programme of school readiness at 4 years of age. Methods: VPT children discharged from Wellington and Auckland Neonatal Intensive Care Units (2005–2009) were compared to a national control cohort born during the same period. Outcome measures included Parental Evaluation of Developmental Status (PEDS), parent and teacher versions of the Strengths and Difficulties Questionnaire (SDQ‐P and SDQ‐T) and vision and hearing screening, and were related to perinatal and demographic characteristics obtained from the Australia and New Zealand Neonatal Network database. Results: Of 1105 VPT children, 920 were matched to the B4SC database, of whom 814 (88%) had one or more B4SC screening outcomes recorded. Compared with controls, VPT children were more likely to have abnormal PEDS (odds ratio (OR) = 1.79, 1.53–2.10), SDQ‐P (OR = 1.82, 1.49–2.23), SDQ‐T (OR = 1.51, 1.10–2.06), vision (OR = 2.00, 1.54–2.60) and hearing (OR = 1.95, 1.65–2.31) screen outcomes. While VPT children with an abnormal screen were more likely to be referred for further assessment, only 34%, 22%, 94% and 51% with abnormal PEDS, SDQ or vision and hearing screen, respectively, had evidence of appropriate referral. School readiness difficulties were significantly associated with birthweight z ‐score ≤ −1, vaginal delivery, significant cranial ultrasound abnormalities, younger maternal age, higher deprivation neighbourhood and ventilation ≥72 h. Conclusion: Community‐based screening may be useful for identifying VPT children with school readiness difficulties, but low referral rates may limit the effectiveness of such programmes.